Multidimensional Sustainability Indicators: Barriers, Drivers and Challenges for Human Development - Deus, Rafael Mattos [UNESP]; Ogasawara Vieira, Karina Rabelo [UNESP]; Franzao, Diego Antonio [UNESP]; Mariano, Enzo Barberio [UNESP] (Univ Federal Campina Grande, Centro Ciencias Juridicas & Sociais, 2017)
With the growing number of indicators that are drawn up and published, there is a force on them that define which will survive, that is, the natural selection of indicators. Thus, this study aims, through a systematic literature review, identify the barriers, drivers, and challenges of found indicators. It was observed that the lack of agreement persists in a significant scientific debate about the dimensions of sustainability. Despite the lack of consensus, it is deemed relevant to each study to define the dimensions of sustainability as its context, which is supported by the diversity of areas that may involve the construction of multidimensional indicators of sustainability. It stands out as barriers, institutional, political and complexity of phenomena involving sustainability. However, as motivators, indicators assist in implementing sustainable policies and improves public administration for human development. The great challenge of multidimensional indicators of sustainability is to be adapted to the local level and avoid subjectivity.
Keywords: Multidimensional Indicators; sustainability; barriers; drivers